2017
DOI: 10.3389/fphar.2017.00913
|View full text |Cite
|
Sign up to set email alerts
|

Purines and Carotid Body: New Roles in Pathological Conditions

Abstract: It is known that adenosine and adenosine-5′-triphosphate (ATP) are excitatory mediators involved in carotid body (CB) hypoxic signaling. The CBs are peripheral chemoreceptors classically defined by O2, CO2, and pH sensors. When hypoxia activates the CB, it induces the release of neurotransmitters from chemoreceptor cells leading to an increase in the action potentials frequency at the carotid sinus nerve (CSN). This increase in the firing frequency of the CSN is integrated in the brainstem to induce cardioresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 148 publications
(272 reference statements)
1
23
0
Order By: Relevance
“…Several pathologies including hypertension, diabetes and obstructive sleep apnea have been associated with changes in carotid bodies activity ( Conde et al, 2017 ). Increase in carotid sinus nerve activity drives excitation in medullary presympathetic pathways and is integrated in the brain stem to induce cardiorespiratory compensatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathologies including hypertension, diabetes and obstructive sleep apnea have been associated with changes in carotid bodies activity ( Conde et al, 2017 ). Increase in carotid sinus nerve activity drives excitation in medullary presympathetic pathways and is integrated in the brain stem to induce cardiorespiratory compensatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Among the neurotransmitters released from the chemoreceptor cells are ATP and adenosine. In the last few years a large body of evidence has demonstrated the significance of adenosine and ATP in the hypoxic chemotransduction in the CB (Buttigieg & Nurse, 2004;Conde et al 2009Conde et al , 2017Murali & Nurse, 2016). The CB releases adenosine and ATP simultaneously in response to hypoxia, the release of ATP and its extracellular catabolism to adenosine being the main origin of extracellular adenosine at high-intensity hypoxia (Conde & Monteiro, 2004;Conde et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from this laboratory demonstrated that 5-HT acts on ketanserin-sensitive 5-HT2Rs on type II cells leading to an increase in intracellular Ca 2+ that appears necessary for the activation of ATP-permeable Panx-1 channels (Murali et al, 2017). ATP is a key excitatory sensory neurotransmitter in the CB, and although type I cells are generally presumed to be the major source of ATP during chemotransduction (Buttigieg & Nurse, 2004;Conde et al, 2017;Conde, Monteiro, Rigual, Obeso, & Gonzalez, 2012;Leonard et al, 2018;Nurse, 2014;Nurse & Piskuric, 2013;, type II cells might provide an alternative pathway for boosting synaptic ATP concentrations and therefore increase the safety factor for purinergic transmission (Leonard et al, 2018;Nurse, 2014;Nurse & Piskuric, 2013;Tse et al, 2012;Zhang et al, 2012). We found that inhibitors of SFK and PKA, but not PKC, reversibly blocked Panx-1-like currents activated by 5-HT in type II cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian carotid bodies (CBs) are sensory organs that play a key role in the maintenance of O 2 and CO 2 /H + homeostasis via the initiation of respiratory and cardiovascular reflexes (Gonzalez, Almaraz, Obeso, & Rigual, 1994;Kumar & Prabhakar, 2012). The purines ATP and adenosine are among a broad spectrum of neurotransmitters/neuromodulators that mediate the increase in afferent discharge during exposure to low O 2 (hypoxia) and elevated CO 2 /H + (hypercapnic acidosis) (Conde, Monteiro, & Sacramento, 2017;Nurse, 2014). Several pathophysiological conditions, including sleep apnoea, c 2018 The Authors.…”
Section: Introductionmentioning
confidence: 99%